Management of Management Information Systems at Jomelo Cosmetic Shop on Bukit Kaminting Induk Street, Palangka Raya City - Nathaly Inglesia; Santi Wati; Rossana Tiara Christin; Riska Pania Putri; Astrid Astrid; Cindy Carolina; Nisrina Rahmi (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
This research explores the management of management information systems at Jomelo Cosmetic Shop on Bukit Kaminting Induk Street, Palangka Raya City using qualitative methods and a holistic approach. Data were collected through observation, interviews, and documentation. The study discovered that the deployment of a management information system has a significant impact on the efficacy of the organization's data source system, with 100% of respondents stating that SIM helps improve operational efficiency and decision-making. In the study, one hundred percent of respondents stated that SIM improves operational efficiency and decision-making processes, which shows how important the implementation of a management information system is to improve the performance of enterprise data source systems. The study recommends several measures to improve the effectiveness and efficiency of management information system, such as increasing staff training on the use of SIM (80% of respondents agreed), monitoring and evaluating SIM performance regularly (75% of respondents agreed) and optimizing the use of information technology to support SIM (65% of respondents agreed). This study also recommends several steps to improve product information for customers, such as providing more complete product information on the store website (90% of respondents agreed), utilizing social media to promote products (85% of respondents agreed), and training store staff to provide proper product information (70% of respondents agreed The findings of this study indicate that Jomelo Cosmetic Shop can improve its competitiveness and quality of service to customers by implementing best practices in information systems management. This is expected to improve operational efficiency and better delivery of product information to customers.